1988
DOI: 10.1128/jvi.62.1.325-330.1988
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the human beta interferon gene by the adenovirus type 12 E1B gene

Abstract: The transcription of endogenous beta interferon mRNA was activated in human embryo kidney (HEK) cells infected with adenovirus type 12 (Ad12) but was activated only inefficiently or not at all in HEK cells infected with Ad5 and rc-1 (Ad5 dl312 containing the Ad12 E1A region). The analysis with Ad12 mutants showed that Ad12 E1B products, especially the 19K protein, were important for the expression of the endogenous beta interferon gene and Ad12 E1A products were not involved in the expression. The expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In contrast, we reported that the transcription of the human beta IFN (IFN-P) gene is dependent on the adenovirus protein in human and chicken cells (21). Recently, some reports showed that the ElB-19K protein could stimulate the transcription of adenovirus ElA and other viral and cellular genes (11,12,21,25).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, we reported that the transcription of the human beta IFN (IFN-P) gene is dependent on the adenovirus protein in human and chicken cells (21). Recently, some reports showed that the ElB-19K protein could stimulate the transcription of adenovirus ElA and other viral and cellular genes (11,12,21,25).…”
mentioning
confidence: 98%
“…E1B (gApB) DNA is pSV2gpt (19) with an Adl2 fused fragment of the ElA promoter region (nucleotides [nt] 11 to 495) and E1B coding region (positions 1536 to 3858) at the EcoRI and the BamHI sites (21), and ElB-19K DNA is the gApB with the ElB-19K coding region (nt 1536 to 2318 and 3138 to 3858) instead of the ElB-coding region. The secondary CEF cells were cotransfected with DNAs by the Polybrene and dimethyl sulfoxide method (13,21). At 40 h after transfection, the cell extract was prepared for the chloramphenicol acetyltransferase (CAT) assay as described previously (9,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Oct-3 expression vector (pCMVOct-3) was constructed by inserting the full-length Oct-3 cDNA (Okamoto et al, 1990) into an expression vector driven by the CMV promoter. The ElA expression vector (referred to as pSVEla; Shiroki and Toth, 1988 Isolation of the hybrd cells and their derivative cell lines 052, a P19 cell line containing a single copy of the enhancer-trap, has previously been described by us (Bhat et al, 1988). An HGPRT-deficient 052 cell line was isolated by selecting 052 cells in the presence of 10 ,M 6-thioguanine, as described by Hooper (1987).…”
Section: Methodsmentioning
confidence: 99%
“…All the hybrid cell lines were sensitive toG418 (200 ug/ml). To isolate 'revertants', one of the hybrid cell lines (Fl) was co-transfected with the Oct-3 expression vector (pCMVOct-3) and the E1A expression vector (pSVEla; Shiroki and Toth, 1988) at various ratios. The transfected cells were exposed to 200 yg/ml ofG418.…”
Section: Methodsmentioning
confidence: 99%